Simultaneous Determination of Isoniazid and Pyridoxine Hydrochloride in Tablet Dosage Forms using Ratio Subtraction Spectrophotometry - Rida Evalina Tarigan; Ester Lince Fiani Mendrofa; Chemayanti Surbakti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The study focused on the simultaneous quantification of Isoniazid (INH) and Pyridoxine Hydrochloride (PRD) in tablet form, commonly used in antituberculosis treatments. Assessing the accurate concentration of both INH and PRD in tablets is vital to ensure their effectiveness, safety, and quality. Using the ratio subtraction spectrophotometry method, the study analyzed INH and PRD in Pehadoxin forte® tablets (batch no. 36057007, PT. Phapros, Indonesia), with 0.1 N HCl as the solvent. The method involved obtaining ratio absorption spectra by dividing the absorption spectra of INH and PRD, respectively, to derive zero-order spectra for each drug. Method validation parameters included linearity, accuracy, precision, Limit of Detection (LOD), and Limit of Quantification (LOQ). The results showed linearity values of 0.9985 for INH and 0.9988 for PRD. Accuracy was 98.1838% for INH and 100.0205% for PRD, while precision was 1.8769% for INH and 0.2037% for PRD. LOD and LOQ for INH were 0.8116 µg/mL and 2.7053 µg/mL, respectively, and for PRD, 1.3127 µg/mL and 4.3757 µg/mL. The levels of INH and PRD in the tablets were found to be 102.1157% and 101.3874%, aligning with the Indonesian Pharmacopoeia's standards. This methodological approach provides a reliable analytical tool for the simultaneous assessment of INH and PRD in tablets, potentially extendable to other drug combinations and formulations, thereby contributing to pharmaceutical quality control processes.